Peran Audit Internal, Deteksi Fraud, dan Pencegahan di Universitas: Tinjauan Pustaka - Nisak, Ifa Azzakyatun; Rochayatun, Sulis (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2023)
From time to time, transparency and accountability in universities have grown wider and encourage universities to make quality reports that are free from fraud. This study examines the role of internal audit in detecting and preventing fraud in universities from a literature and empirical review side based on the existing literature and supported by empirical data generated from previous research. Data collection techniques were carried out by searching for relevant articles through databases on Emerald, Springer, and Google Scholar by emphasizing keywords related to the theme. The study results show that an empirically internal audit is needed to detect and prevent university fraud. Internal audits must assist universities in implementing effective controls by assessing effectiveness and efficiency and urging universities to make continuous improvements. Internal audit helps universities achieve their goals by designing, evaluating, and improving risk management, university governance procedures, and the effectiveness of university controls. Internal audit in universities also serves as a supervisor in preventing and detecting fraudulent activities. The implications of this study are expected to be used as evaluation material to maximize the role of internal audits in universities so that they can detect and prevent fraud.